Drying Characteristics of Cayenne Pepper (Capsicum frutescens L.) Using a Rotary Rack Hybrid Dryer with Blanching Pretreatment Application - Ida Ayu Widhiantari; Sukmawaty Sukmawaty; Murad Murad; Muh Yustiar Arrohman; Alifkha Bagus Sandhiyana; Gunawan Gunawan (The University of Lampung, 2025)
Proper post-harvest handling is very necessary to maintain product quality and extend the shelf life. One way to extend the shelf life of agricultural products, including cayenne pepper (Capsicum frutescens L.), is by drying techniques. Blanching pretreatment before drying can maintain the condition of the dried product so that it can maintain the final product quality. The aim of this research was to analyze the water content, water content ratio (MR), drying rate, drying constant of cayenne pepper using a rotary rack type of hybrid dryer. The use of rotary racks type hybrid dryer is a cheaper drying alternative and the use of rotary racks is able to standardize the water content in the cayenne pepper drying process. The research was carried out with two treatments, namely with and without blanching process at a temperature of 90°C for 5 min. The second factor was drying temperatures were are 43 47℃, 48-52℃ and 53-57℃ until the cayenne pepper reach the water content according to the reference, namely in the range of 5-8%. From the research results, it was obtained that the lowest water content of cayenne pepper was given pretreatment blanching at a temperature of 53-57°C, namely 6.43% with a drying time of up to 14 h. The drying rate of blanched cayenne pepper was higher than that of unblanched cayenne pepper. Keywords: Blanching, Cayenne pepper, Drying.